MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN DI SDN 73/VI TANJUNG DALAM KECAMATAN LEMBAH MASURAI - Sastra, Ali; Maulana Putra, Ikhsan (Jurnal Muara Olahraga, 2024)
Abstract In this research, the problem that the author found when conducting observations in the field was that students' motivation was still low in learning physical education, sports and health at SDN 73/VI Tanjung Dalam Lembah Masurai District. There are many factors that influence the learning process in physical education, sports and health, one of which is the motivation factor. This type of research is descriptive. The aim of this research was to determine students' motivation in learning physical education, sports and health at SDN 73/VI Tanjung Dalam Lembah Masurai District. The population in this study was 58 students at SDN 73/VI. Samples were taken using random sampling technique, with a total sample of 38 people. directly by researchers by submitting questionnaires to students. Meanwhile, secondary data is taken from student documentation archives from School Administration. Next, the data was analyzed by percentage using the ideal value score. Based on the results of data analysis, it shows that the variable intrinsic motivation of students at SDN 73/VI Tanjung Dalam Lembah Masurai District, obtained an achievement level of 84.70%, with a "Good" classification. Meanwhile, the extrinsic motivation of students at SDN 73/VI Tanjung Dalam Lembah Masurai District, achieved an achievement level of 83.07%, which was classified as "Good". Keywords: Intrinsic Motivation, Extrinsic Motivation